Anti‐Proliferative 1, 4‐Dihydropyridine and Pyridine Derivatives Synthesized through a Catalyst‐Free, One‐Pot Multi‐Component Reaction. Issue 43 (19th November 2018) - Sharma, Mayank G.; Vala, Ruturajsinh M.; Patel, Divyang M.; Lagunes, Irene; Fernandes, Miguel X.; Padrón, José M.; Ramkumar, Venkatachalam; Gardas, Ramesh L.; Patel, Hitendra M.
Abstract: In this study, we explored the catalyst‐free one‐pot multi‐component synthesis of 1, 4‐dihydropyridine derivatives by following green chemistry protocol. The present approach shows the significant outcomes such as yield up to 94%, catalyst‐free reaction, easy workup procedure and shorter period of reaction time. In this work we also highlighted the comparison of the yields obtained under both neat and solvent media as well. The anti‐proliferative activity of all newly synthesized compounds has been assessed against six human solid tumor cell lines. Seven compounds show good activity against single cell line whereas, compounds having a pyridine scaffold showed significant anti‐proliferative activity. Abstract : An expedient synthesis of 1, 4‐dihydropyridines (DHPs) and pyridines under catalyst‐free condition is explored with excellent reaction yield up to 94%. All newly synthesized compounds were screened for anti‐proliferative activity against different human tumor cell lines. The remarkable results on yield, process, development of DHPs, anti‐proliferative activity, structure determination and single crystal study of DHPs discussed in this article.